The Rosetta Stone Espanol level 1 [and] level 2 - Fairfield Language Technologies (Firm) (Harrisonburg, VA : Fairfield Language Technologies, 2002)
A comprehensive language learning solutions for private, educational and professional use. With complete curriculum management, networking and record-keeping capabilities.
Keywords: Spanish language; Spanish language -- Computer-assisted instruction for foreign speakers -- software